Syrian Asylum Seekers as Political Factors and Their Effects on Local Politics - Levent Börklüoğlu; Ali Utku Şahin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The influx to Turkey amidst the 2011 Syrian civil war has significantly affected the Syrian and Turkish communities socially and economically. It can be claimed that this major Syrian existence among Turkish society, has the potential to be a factor, especially in local politics and the political choices of Turkish citizens. The study focuses on 12 provinces of Turkey where the ratio of Syrian asylum seekers to the population of the province is the highest in Turkey. The main subject of this study is the function of Syrian asylum seekers in structuring Turkey’s local politics. Within this context and based on the last two local elections in Turkey, election manifests and speeches of political parties and mayoral candidates are analyzed on the axis of Syrian asylum seekers. Also, the distinctive role of the presence of Syrian asylum seekers and political discourse about them in the political choices of Turkish voters is presented argumentatively. In this study, data obtained through content analysis is analyzed within a comparative framework, and in consequence, the functions of Syrian asylum seekers as political factors in structuring local politics are evaluated.